The Modular µSiM Reconfigured: Integration of Microfluidic Capabilities to Study In Vitro Barrier Tissue Models under Flow. Issue 21 (21st August 2022) - Mansouri, Mehran; Ahmed, Adeel; Ahmad, S. Danial; McCloskey, Molly C.; Joshi, Indranil M.; Gaborski, Thomas R.; Waugh, Richard E.; McGrath, James L.; Day, Steven W.; Abhyankar, Vinay V.
Abstract: Microfluidic tissue barrier models have emerged to address the lack of physiological fluid flow in conventional "open‐well" Transwell‐like devices. However, microfluidic techniques have not achieved widespread usage in bioscience laboratories because they are not fully compatible with traditional experimental protocols. To advance barrier tissue research, there is a need for a platform that combines the key advantages of both conventional open‐well and microfluidic systems. Here, a plug‐and‐play flow module is developed to introduce on‐demand microfluidic flow capabilities to an open‐well device that features a nanoporous membrane and live‐cell imaging capabilities. The magnetic latching assembly of this design enables bi‐directional reconfiguration and allows users to conduct an experiment in an open‐well format with established protocols and then add or remove microfluidic capabilities as desired. This work also provides an experimentally‐validated flow model to select flow conditions based on the experimental needs. As a proof‐of‐concept, flow‐induced alignment of endothelial cells and the expression of shear‐sensitive gene targets are demonstrated, and the different phases of neutrophil transmigration across a chemically stimulated endothelial monolayer under flow conditions are visualized. With these experimental capabilities, it is anticipated that both engineering and bioscience laboratories will adopt this reconfigurable design due to the compatibility with standard open‐well protocols. Abstract : Although Transwell‐like platforms are the gold standard for creating tissue‐barrier models in bioscience laboratories, they lack physiological fluid flows. In this work, a static open‐well culture platform‐featuring a 100 nm thick nanoporous membrane‐is reconfigured between static and flow‐enhanced culture modes to increase experimental flexibility. Using this platform, upregulation of shear‐responsive genes and dynamics of neutrophil transmigration across an endothelial barrier under flow conditions are demonstrated.